(untitled) (Research, Society and Development, 2022)
The success of antiretroviral therapy, which culminates in an increase in the survival of people living with HIV/AIDS (PLWHA), results in an increase in the demand for oral health care. From this perspective, it is extremely important to invest more in educational actions that expand the dissemination of information, which directly contribute to the reduction of damage and prevention of diseases, so that the more quality information that is made available by different vehicles, the greater the access and, consequently, the impacts of such actions on these people’s lives. The objective of this work is to synthesize the scientific evidence present in the literature, regarding health education for people living with HIV/AIDS. This is an integrative literature review study, guided according to the guidelines of the Jonna Briggs Institute (JBI, 2020), in which the study question was elaborated using the Population, Concept and Context (PCC) strategy, being in this way organized: “What is the scientific evidence regarding health education actions for people living with HIV/AIDS?”. The bibliographic survey was carried out in the following databases: Scientific Electronic Library (SCIELO), National Library of Medicine (PubMed) and Google Scholar. After applying the inclusion and exclusion criteria, 6 articles were selected for characterization. It is concluded that, currently, there is a scarcity of studies that contextualize the application of health education for PLWHA, justifying the relevance of research investment in this theme.